HER2 expression in gastric and oesophageal cancer: a meta-analytic review - Nagaraja, Vinayak; Eslick, Guy D. (Journal of Gastrointestinal Oncology; Vol 6, No 2 (April 13, 2015): Journal of Gastrointestinal Oncology, 2015)
Background: Since the advent and the success of adjuvant medical therapy for human epidermal growth factor receptor 2 (HER2)-positive breast cancer in the form of trastuzumab there has been increasing interest in the development of similar therapies in other solid organ malignancies including gastric cancer and oesophageal cancer. Over the years, multiple observational studies have been inconsistent. Several meta-analyses have been published looking at the association between HER2 and gastric cancer and oesophageal cancer. This review aims to summarize the meta-analytic evidence for the association between HER2 in gastric and oesophageal cancer. Methods: A systematic search was conducted using MEDLINE, PubMed, EMBASE, Current Contents Connect, Cochrane Library, Google Scholar, Science Direct, and Web of Science. Results: Of the articles selected, only nine studies met full criteria. Six of them reviewed the role of HER2 in gastric cancer and the remaining three reviewed its role in oesophageal cancer. Conclusions: The current evidence regarding the role of HER2 is unclear. However, it clearly plays a key role in the pathogenesis of gastric and oesophageal carcinomas. Targeted therapy towards this subgroup (despite variable frequency and association with survival) would offer a mortality benefit and improve survival.